Gender in livestock development: Julius Githinji - Githinji, Julius (International Livestock Research Institute, 2019)
Julius Githinji, research assistant at ILRI, shares his 'aha' moment when he really understood the central importance of women in livestock development. This film was produced to mark the International Women’s Day 2019 which is themed ‘Think equal, build smart, innovate for change’.